69.4k views
1 vote
Solve 4x – 2(x + 1) = 3x + 10.

User Davitenio
by
5.0k points

2 Answers

7 votes

Answer:

x=-12

Explanation:

4x-2x-2=3x+10

2x-2=3x+10

2x-2+2=3x+10+2

2x=3x+12

2x-3x=3x+12-3x

-x=12

-x/-1 = 12/-1

x= -12

User Tomdelahaba
by
5.8k points
4 votes

Answer:

x=-12

Explanation:

4x−2(x+1)=3x+10

Step 1: Simplify both sides of the equation.

4x−2(x+1)=3x+10

4x+(−2)(x)+(−2)(1)=3x+10(Distribute)

4x+−2x+−2=3x+10

(4x+−2x)+(−2)=3x+10(Combine Like Terms)

2x+−2=3x+10

2x−2=3x+10

Step 2: Subtract 3x from both sides.

2x−2−3x=3x+10−3x

−x−2=10

Step 3: Add 2 to both sides.

−x−2+2=10+2

−x=12

Step 4: Divide both sides by -1.

−x/−1=12/−1

x=−12

Answer:

x=−12

User Travis Tidwell
by
4.8k points